Phacoemulsification Complicated Subluxation of the Crystalline Lens, Anterior Megalophthalmos, Central Cloudy Corneal Dystrophy of Francois and High Myopia - B. E. Malyugin; A. Yu. Menshikov; R. S. Isabekov; S. Yu. Kalinnikova; I. S. Tkachenko (Oftalʹmologiâ, 2023)
A case is described of a 47-old man with anterior megalophthalmos, high myopia (>31.0 mm) and who underwent bilateral consecutive phacoemulsification. In addition a bilateral dislike corneal opacity was present which was classified as central cloudy corneal dystrophy of Francois. Special attention must be paid to both surgical technique and IOL selection. In the first eye a single-piece foldable IOL was implanted into a capsule bag, in the second eye three-piece foldable IOL were sutured fixed to the iris. In the meantime, phacoemulsification in patients with dystrophy of Francois safe and does not lead to progression. We calculated the IOL power for our case with the Haigis and Barret II Universal formula retrospectively.